2016
DOI: 10.1016/j.aei.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A people-centric sensing approach to detecting sidewalk defects

Abstract: A defective sidewalk inhibits the walkability of a street and may also cause safety accidents (slips, trips, and falls) for pedestrians. When a pedestrian walks along a sidewalk, his/her behaviors may vary according to the condition of the sidewalk-e.g., whether the surface is normal, holed, cracked, tilted, or sloped. As a result, the pedestrian's stability may also change according to the built environment's conditions. Accordingly, this paper examines the feasibility of using pedestrians' physical behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 47 publications
2
66
0
Order By: Relevance
“…The physiological responses of older adult pedestrians can be reflective of human experience toward a surrounding environment, providing us unique insights into the elements of the urban built environments (e.g., neighborhood disorders and environmental barriers) ( 19 23 ). Various types of physiological response data including gait patterns, electrodermal activity (EDA), heart rate and brain activity ( 22 , 24 26 ) have been have been investigated from collected physiological signals in virtual environments ( 27 29 ) naturalistic ambulatory settings and daily life locations, such as neighborhoods, downtown, urban parks, and university campuses ( 18 , 20 , 22 , 23 , 30 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological responses of older adult pedestrians can be reflective of human experience toward a surrounding environment, providing us unique insights into the elements of the urban built environments (e.g., neighborhood disorders and environmental barriers) ( 19 23 ). Various types of physiological response data including gait patterns, electrodermal activity (EDA), heart rate and brain activity ( 22 , 24 26 ) have been have been investigated from collected physiological signals in virtual environments ( 27 29 ) naturalistic ambulatory settings and daily life locations, such as neighborhoods, downtown, urban parks, and university campuses ( 18 , 20 , 22 , 23 , 30 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the gait pattern has been shown to correlate with physical barriers of urban built environments such as sidewalk defects, curbs, slopes, and holes ( 19 23 , 43 52 ) (See Table 1 ). Signals, such as electrodermal activity ( 18 , 21 25 , 27 31 , 36 – 42 ), electrocardiography or photoplethysmography ( 18 , 20 23 , 28 , 36 – 40 , 52 , 53 ) and brain activity ( 26 , 32 , 40 , 54 , 55 ), have been separately used to understand psychological states toward stressors in relation to negative environmental stimuli (e.g., broken houses, barking dogs, and steep stairs) and the mood of walking paths such as urban busy and quiet areas ( 23 , 30 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The promotion of physical activity (PA) in the general population is an essential factor that improves public health [ 1 , 2 ]. Numerous previous studies have shown how the built environment influences the behavior of pedestrians [ 3 , 4 , 5 , 6 , 7 , 8 ]. As the most widely practiced form of both transportation and PA, walking and the walking environment have been the focus of many studies [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To identify and address environmental barriers, governmental agencies have undertaken various approaches including inspection by experts and encouraging individuals to self-report [ 8 , 28 ]. In these approaches, inspectors observe the built environment to identify potential environmental barriers and individuals report the environmental features that can act as environmental barriers in their daily living [ 8 , 28 , 29 , 30 , 31 , 32 ]. Although these approaches can identify and create a list of potential environmental barriers, there may be several problems in the process of identifying these impediments.…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap, the authors propose the collective sensing (Yang et al, 2017). The collective sensing synthesizes a group of people's signals of interest with location data (e.g., global positioning system (GPS) data) simultaneously to identify locations on which abnormal patterns in the signal occur across the multiple people (Kim et al, 2016;Yang et al, 2017). While a person's stress can be caused by various stimuli, collective stress, which is defined in this study as stress commonly sensed from multiple people on a specific location, can be indicative of a locational stress-inducing factor on the location such as environmental barriers.…”
Section: Introductionmentioning
confidence: 99%